PEMBERDAYAAN PENGELOLA OBJEK WISATA KAMPUNG LEBAH MURPEJI MELALUI PELATIHAN PEMBUATAN PAKET WISATA - Fathurrahim, Fathurrahim; Mila Sari; Anggi Maulida; Zombie Kaswari Wantira; Baiq Siti Rahmi Nur lita; Lalu Ibnu; Oki Sastrawan; Pandu Wijaya; Muh Hayyi; Hamdani, Hamdani (Bajang Institute, 2025)
Kampung Lebah Murpeji, part of Dasan Geria Village in Lingsar District, West Lombok Regency, holds significant potential to be developed as a tourist destination. This potential lies primarily in the unique trigona bee farming, the scenic mountainous landscape, and local wisdom values. However, the lack of professional management of the tourist destination remains a major challenge. This article discusses efforts to develop Kampung Lebah Murpeji through a training program on creating tourism packages. The training aims to enhance the skills of local communities in designing, managing, and promoting tourism packages. The results indicate increased community participation and the formation of several flagship tourism packages. In conclusion, this training has proven effective in enhancing Kampung Lebah Murpeji’s appeal as an ecotourism destination